Effects of Increasing Levels of Copper from Either CuSO4 or Combinations of CuSO4 and a Cu-Amino Acid Complex on Growth Performance, Carcass Characteristics, and Economics of Finishing Pigs - C. B. Carpenter; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; Z. J. Rambo (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 1,089 pigs (PIC 280 ×1050; initially 82.2 lb) were used in a 105-d experiment to determine the effects of increasing added Cu from either CuSO4alone or a 50/50 blend of CuSO4and Cu-AA (Availa®-Cu, Zinpro Corporation, Eden Prairie, MN) on growth performance, carcass characteristics, and economics of finishing pigs. All 6 dietary treatments contained 17 ppm Cu from CuSO4from the trace mineral premix. Additional treatment diets contained added CuSO4to provide 70 and 130 ppm total Cu or a 50/50 blend of added Cu from CuSO4and Cu-AA to provide 70, 100, and 130 ppm total Cu. There were 25 or 26 pigs per pen and 7 replicate pens per treatment. Overall, added Cu above 17 ppm did not influence ADG; however, pigs fed 70 and 130 ppm added Cu from the 50/50 blend of CuSO4and Cu-AA had decreased (P = 0.045) ADFI and improved feed efficiency (P = 0.048) compared with those fed 70 and 130 ppm of added Cu from CuSO4only. Similar to the F/G response, pigs fed diets that contained CuSO4alone had poorer (P = 0.030) carcass F/G than those fed added Cu from the 50/50 blend of CuSO4and Cu-AA. Neither Cu source nor level influenced economics. In conclusion, these data suggest pigs fed diets that contained added Cu from CuSO4alone consume more feed but have poorer feed efficiency which translates into poorer carcass F/G compared to those fed a 50/50 blend of CuSO4and Cu-AA. Copper level did not impact growth performance. Based on our study, it appears that the 50/50 blend of CuSO4/Cu-AA optimized feed efficiency and carcass feed efficiency of pigs marketed on a constant time basis.
Keywords: carcass characteristics; copper; finishing pig; growth; level; source